ASR, Volume 20, n° 2, 2016 - Full Issue - journal system, (African Sociological Review, 2016)
Contents Editorial ....................................................1 General Issue Reality Checks: The state of civil society organizations in Ethiopia Yntiso Gebre ...............................................2 Re-Conceptualizing the impact of development on childcare: The Volta River Project and the child survival challenge in Dzemeni Kodzo Atakuma Agbodza .......................................................26 Youth Violence Theories: Developing interventions to promote sustainable peace in Ilorin, Nigeria Ali Arazeem Abdullahi, Mariam Seedat-Khan, Saheed, Olanrewaju, Abdulrahman .................................40 Research Papers La participation citoyenne en contexte local au Cameroun. Entre demande de légitimité, efficacité versatile et tensions politiciennes. Calvin Minfegue ..................................................61 Corporate social responsibility and workers’ well-being in Nigerian banks Joseph A. Oluyemi, Muhammed A. Yinusa, Rajw Abdulateef and Ibimidu Akindele ..................................89 A qualitative application of Amartya Sen’s ‘development as freedom’ theory to an understanding of social grants in South Africa. Mzingaye Brilliant Xaba ...........................................102